Exploring geographic variation in acute appendectomy in Ireland: results from a national registry study - Jan Sørensen; Ola Ahmed; Ken Mealy (BMJ Open)
Objective To explore geographic variations in Irish laparoscopic and open appendectomy procedures.Design Analysis based on 2014–2017 administrative hospital data from public hospitals.Setting Counties of Ireland.Participants Irish residents with hospital admissions for an appendectomy as the principal procedure.Main outcome measures Age and gender standardised laparoscopic and open appendectomy rates for 26 counties. Geographic variation measured with the extremal quotient (EQ), coefficient of variation (CV) and the systematic component of variation (SCV).Results 23 684 appendectomies were included. 77.6% (n= 18,387) were performed laparoscopically. An EQ of 8.3 for laparoscopy and 10.0 for open appendectomy was determined. A high CV was demonstrated with a value of 36.7 and 80.8 for laparoscopic and open appendectomy, respectively. An SCV of 14.2 and 124.8 for laparoscopic and open appendectomy was observed. A wider variation was determined when children and adults were assessed separately.Conclusions The geographic distribution in rates of appendectomy varies considerably across Irish counties. Our data suggest that a patient’s likelihood of undergoing a laparoscopic or open appendectomy is associated with their county of residence.